Shift in living kidney donor demographics over the past 50 years in a German transplant center - Sommerer, Claudia; Bougioukou, Zoi; Georgiou, Vasileios L.; Mehrabi, Arianeb; Zeier, Martin (Annals of transplantation, 2021)
BACKGROUND - Living kidney donors may face health risks after donation. Age, sex, body mass index, comorbidities, and relationship to the recipient have an impact on lifetime living kidney donor risk. In view of a changing landscape in renal transplantation with increasing organ shortages, the selection criteria for potential donors may have changed over time. - MATERIAL AND METHODS - We investigated donor demographics and outcomes in a cohort of 760 living kidney donors who donated from 1967 to 2016 at the transplant center in Heidelberg, Germany. - RESULTS - The living kidney donor age increased from 34.9±11.5 to 53.2±10.2 years, with 11.4% donors aged 65 years in the period from 2011 to 2016. The number of donors with comorbidities at the time of donation increased. The percentage of donors with a history of obesity, hypertension, smoking, and a family history of kidney disease enlarged to 18.6%, 36.1%, 37.0%, and 9.1%, respectively. De novo hypertension was a common problem in more than half of the donors at long-term follow-up, and donor renal function decreased about 30 mL/mi/1.73 m². - CONCLUSIONS - This detailed analysis of living kidney donor demographics over the last 50 years detected an increased proportion of donors with higher age and comorbidities today. Careful donor selection, regular follow-up visits, and systematic donor registries are required to further improve donor outcomes.
Gesehen am 15.07.2021